A Comparison of Commercially Available Digital Microscopes for Their Use in Bench-Model Simulation of Microsurgery - Awad, Laura; Abdi, Zakee; Langridge, Benjamin J.; Karoshi, Akul; Butler, Peter E. M. (Journal of Reconstructive Microsurgery, 2024)
Background Surgical education has seen a transition in the delivery of training, with increased use of online platforms to facilitate remote learning. Simulation training can increase access to education and reduce cost implications, while reducing patient risk. This study aims to compare commercially available digital microscopes, alongside a standard binocular surgical microscope, and determine whether they can be used as an alternative tool for remote microsurgery simulation.Methods Data were collected for a total of four microscopes, including three commercially available digital microscopes, smartphone, and a binocular table microscope. Product characteristics were collated, and a subjective assessment was conducted using an 11-criteria questionnaire, graded with a 5-point scale. Results of digital microscopes were compared with the table binocular microscope.The Kruskal–Wallis test was used to compare the performance of digital microscopes to the standard binocular microscopeResults The questionnaire was completed by 31 participants: two consultants, nine surgical registrars, fourteen junior trainees, and six medical students. Digital microscopes were found to be significantly more affordable and convenient for trainees; however, the cost of the smartphone was significant. Overall, the Pancellant Digital Microscope performed the poorest, with trainees commenting on its unsuitability for surgical practice; the Plugable USB Digital Microscope (PLDM) was rated overall most like the binocular table microscope. The Depth of field was shallow in all digital microscopes.Conclusion With the increasing role of remote learning and simulation training in surgical education, the PLDM can provide a cheaper, more accessible alternative for junior trainees, in their pursuit of microsurgical skill acquisition.
Keywords: microsurgery simulation; microscope; remote learning; surgical simulation